Ethical Review of Research on Human Subjects at Unilever: Reflections on Governance. (10th July 2013) - Sheehan, Mark; Marti, Vernon; Roberts, Tony
Abstract This article considers the process of ethical review of research on human subjects at a very large multinational consumer products company. The commercial context of this research throws up unique challenges and opportunities that make the ethics of the process of oversight distinct from mainstream medical research. Reflection on the justification of governance processes sheds important, contrasting light on the ethics of governance of other forms and context of research.